LEXICAL RICHNESS IN INDONESIAN JUNIOR HIGH SCHOOL STUDENTS’ WRITING PRODUCTION: A CORPUS-BASED STUDY - David Geba Abi Anandi; Fransiskus Xaverius Mukarto (STKIP Siliwangi, 2023)
In the 2013 curriculum, English is not a compulsory subject in primary schools. Students may still have relatively very limited productive vocabulary and they might use certain communicative strategy when they did not know the vocabulary to express themselves. Therefore, this present study aims to examine the lexical richness of junior high school students’ writings on descriptive texts. The study focused on examining the lexical variation, lexical diversity, and lexical sophistication in the students’ writing production. The study was a corpus-based one. The corpus consists of 18 descriptive texts written by junior high school students in Yogyakarta and analyzed using lextutor, a web concordance English v.9 available on the internet. The results of the analysis reveal that descriptive texts have low, but very likely proper, average ratio on lexical variation, lexical density, and lexical sophistication considering their English proficiency level. It should be noted that the students were those of grade 7.